Disturbance to Myristica swamps: Influence on Specific Gravity and Fibre Length of an Endemic and Endangered Tree Species of Western Ghats - Tambat, B.; Murthy, N. Rajaskekar; Gowda, K. N. Muniswamy; Chaithra, G. N.; Sethy, Anil K.; Murthy, M. Mahadev (International Journal of Bio-resource and Stress Management, 2019)
Gymnacranthera canarica (King) Warb is an important tree species associated with Myristica swamps in the Western Ghats. The species is endemic to Western Ghats, India and economically important as fruit mace is used as spice. It is distributed all along the Western Ghats and already listed as threatened. It represents obligate swampy species and helps to understand the response of swampy species to disturbances. In this study an attempt was made to assess the influence of disturbance on swampy species wood specific gravity and fibre length. Using increment borer wood core samples were collected from selected locations in central Western Ghats. The samples were processed in the laboratory and wood specific gravity and fibre length was assessed. Then it was compared across the less disturbed and highly disturbed swamps at six locations. The results indicated that in all the six locations specific gravity decreases with increased level of disturbance to swamps. However, the results were significant at only two locations namely Thorme and Sampaje. The frequency distribution of specific gravity values was positively skewed for the less disturbed swamps whereas it was negatively skewed for highly disturbed swamps. The fibre length had also showed similar pattern. In conclusion our study indicates that disturbance to swamps alters the wood specific gravity and fibre length of swamp associated tree species. Our finding would help in developing long term strategies and action plans for conservation of swamps and its constituent species.